The Relationship Between Emotional Support With Psychological Well-Being In Students In Vocational High Schools: Hubungan Antara Dukungan Emosional Dengan Psychological Well-Being Pada Peserta Didik Di Sekolah Menengah Kejuruan - Faizatul Agustina; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the relationship between emotional support and psychological well-being in students. This research method is quantitative with a correlational approach. The variables in this study are emotional support as the independent variable and psychological well-being as the dependent variable. This research was conducted at SMKN 1 Grati with a sample of 333 students who were taken by the sampling method used was probability sampling method with simple random sampling technique. namely the sampling technique by providing equal opportunities for each element. Data analysis was performed by Pearson product moment correlation analysis using SPSS 23 for windows program. The results showed that there was a positive relationship between emotional support and psychological well-being for students at SMKN 1 Grati. The results showed that the correlation coefficient was 0.562 with a significance level of 0.000 <0.05, which means that the hypothesis in this study can be accepted. With an effective contribution of 31.6%, which means that emotional support affects the level of psychological well-being of students.